2014
DOI: 10.7314/apjcp.2014.15.20.8951
|View full text |Cite
|
Sign up to set email alerts
|

Distribution Characteristics of 3,369 Chinese Colorectal Cancer Patients for Gender, Age, Location and Tumor Size During Colonoscopy

Abstract: Background: Studies have shown the existence of gender-and age-related differences in the incidence and anatomic distribution of colorectal cancers. The purposes of this study were to analyze the distribution characteristics of colorectal cancer patients regarding gender, age, location and tumor size in the course of colonoscopy. Materials and Methods: All colorectal cancer patients who underwent colonoscopy in the First Affiliated Hospital of Guangxi Medical University from 2003 to 2012 were included in our r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
6
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 28 publications
4
6
0
1
Order By: Relevance
“…Our results are consistent with those observed in China and Africa, where the most affected site is the rectum and the least reached one is proximal colon [40,47,64]. This is not the case in developed countries as in the USA and Canada, where the most affected site is the proximal colon followed by the rectum [5,48,50,60,65].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our results are consistent with those observed in China and Africa, where the most affected site is the rectum and the least reached one is proximal colon [40,47,64]. This is not the case in developed countries as in the USA and Canada, where the most affected site is the proximal colon followed by the rectum [5,48,50,60,65].…”
Section: Discussionsupporting
confidence: 91%
“…Patients over 50 years old accounted for 75%, which is close to that observed in Morocco (75%) and China (72%) [38,40,47], but remains lower than Westernized countries where over 90% of CRCs occur in people over 50 years [5,[48][49][50]. The proportion of patients under 40 years (9%), observed in this study is higher compared with those observed in developed countries such as the USA and France, where CRC in young patients is very rare before 40 years and accounts for 1-4% [44,48,50].…”
Section: Discussionsupporting
confidence: 73%
“…We did not find any difference in the distribution of tumor (rectum vs. colon) between young and non-Young CRC groups, similar to findings from other studies looking at early onset CRC (Hav et al, 2011;Quach & Nguyen, 2012) or overall CRC cases (Cai et al, 2014). However a study from the United States reported a higher incidence of rectal cancer in persons younger than 50 years compared to older adults (Fairley et al, 2006), and several other studies have reported increasing incidence of rectal cancer among the younger population (Siegel et al, 2009;Meyer et al, 2010;Ahnen et al, 2014).…”
Section: Discussionsupporting
confidence: 91%
“…Right sided colon cancers usually present among the elderly and many believe that they have more advanced stage at the time of diagnosis [ 12 - 14 ]. In contrast to our findings, the proportion of female patients with cecum adenocarcinoma was higher in several other studies [ 4 , 15 , 16 ].…”
Section: Discussionmentioning
confidence: 99%